Clinical Outcomes of Diabetic Patients with and without Hypertension Vaccinated with the Sinovac Vaccine - Ngarso, Sofia; Ramatillah, Diana Laila; Zaman Huri, Hasniza (Newinera Publisher, 2024)
Diabetes and hypertension are the most common degenerative diseases found during the Covid-19 vaccination. Of the 1488 cases of patients exposed to the Covis-19 virus, 13.2% died with hypertension and 11.6% with diabetes. This study aims to evaluate the clinical outcomes of diabetic and diabetic patients with hypertension who have been vaccinated with the Sinovac vaccine. This study uses retrospective and prospective cohort methods for 5 months. Of the 300 patients, 56.3% were female patients with the majority of the ages coming from the 41 to 60 years old group (46.7%) and 47.6% from the >60 years age group. There was no significant association between the length of diagnosis of diabetic patients and diabetes with hypertension and clinical outcomes. There was an association between kidney failure and clinical outcomes with the death of 8 people (2.7%) in patients with stage 4 and 5 renal failure. There was no association between sociodemographics and clinical outcomes. In comorbidities with Diabetes Mellitus, 3.33% of patients die. From the results of the study, it is also known that patients diagnosed with the disease >10 years have a higher percentage of mortality compared to patients diagnosed <10 years.